A convenient screening method to differentiate phenolic skin whitening tyrosinase inhibitors from leukoderma-inducing phenols. Issue 1 (October 2015) - Ito, Shosuke; Wakamatsu, Kazumasa
Highlights: Oxidation of phenols to ortho -quinones is followed by spectrophotometry and HPLC. Leukoderma-inducing phenols are oxidized by mushroom tyrosinase to toxic ortho -quinones. Phenolic tyrosinase inhibitors are not (or only slowly) oxidized by tyrosinase. Tyrosinase inhibitors should be examined as substrates if they are phenolic compounds. Abstract: Background: Tyrosinase is able to oxidize a great number of phenols and catechols to form ortho -quinones. Ortho -quinones are highly reactive compounds that exert cytotoxicity through binding with thiol enzymes and the production of reactive oxygen species. Certain phenolic (and catecholic) compounds are known to induce contact/occupational leukoderma through activation to ortho -quinones. Objective: We report a convenient screening method to follow the oxidation of those leukoderma-inducing phenols by mushroom tyrosinase. Methods: Oxidation of phenolic compounds by mushroom tyrosinase was followed periodically by UV–vis spectrophotometry. The production of ortho -quinones were confirmed by their absorptions around 400–420 nm. HPLC analysis after reduction with NaBH4 detected the corresponding catechols. Results: Leukoderma-inducing phenols, rhododendrol, raspberry ketone, 4-methoxyphenol, 4-benzyloxyphenol, 4- tert -butylphenol, and 4- tert -butylcatechol, were readily oxidized by mushroom tyrosinase to form ortho -quinones. On the other hand, phenolic skin whitening tyrosinase inhibitors, ellagic acid, 4- n -butylresorcinol, potassium 4-methoxysalicylate, and 2, 2′-dihydroxy-5, 5′-di- n -propylbiphenyl, were not oxidized by mushroom tyrosinase, while arbutin was only slowly oxidized. Conclusion: This study has provided a convenient screening method to differentiate phenolic skin whitening tyrosinase inhibitors from leukoderma-inducing phenols. A common chemical feature of the latter group of compounds is that they are readily oxidized by tyrosinase to form reactive ortho -quinone species. The present results point out the necessity that tyrosinase inhibitors should also be examined as substrates if they are phenolic compounds.